2019
DOI: 10.29271/jcpsp.2019.03.214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Desloratadine Citrate Disodium on Serum Immune Function Indices, Inflammatory Factors and Chemokines in Patients with Chronic Urticaria

Abstract: were selected as study subjects. Inclusion criteria were clinically diagnosed as chronic urticaria, with symptoms and signs of urticaria 24 hours before the experiment; and no other antihistamines, anticholinergic agents, receptor agonists, aspirin drugs or glucocorticoids taken within 2 weeks. Exclusion criteria were pregnant women, lactating women, women of childbearing age who planned to have children in the near future;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Unfortunately, for patients that trial alternative medicine, their reported response rates are even lower with only 20-29% of patients reporting benefit in our study. This would be consistent with the inconclusive studies in acupuncture and traditional Chinese medicine [19][20][21][22][23]. Although, 21% of our patients reported visiting a naturopath, we could not find any studies in the literature that have studied the use of and effectiveness of naturopathic therapies in the treatment of CSU.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Unfortunately, for patients that trial alternative medicine, their reported response rates are even lower with only 20-29% of patients reporting benefit in our study. This would be consistent with the inconclusive studies in acupuncture and traditional Chinese medicine [19][20][21][22][23]. Although, 21% of our patients reported visiting a naturopath, we could not find any studies in the literature that have studied the use of and effectiveness of naturopathic therapies in the treatment of CSU.…”
Section: Discussionsupporting
confidence: 87%
“…There has been some studies that looked at acupuncture for global symptom improvement when used in conjunction with pharmacologic therapy however a recently published meta-analysis showed there is overall a low level of evidence for its use [19]. There has also been a few randomized trials that have looked at the use of traditional Chinese medicine as an adjunct to traditional pharmacologic therapy in CSU with varying results [20][21][22][23]. However, to our knowledge, there has not been any studies that have evaluated patient uptake of these alternative medicine practices and their perceived benefit.…”
mentioning
confidence: 99%
“…Various factors such as genetics, environment, and lifestyle can influence the levels of these cytokines, affecting the incidence, development, and severity of the disease. For instance, Wang et al [18] proved that elevated IL-4 can promote B cell proliferation and immunoglobulin E production, leading to increased sensitivity to allergens and exacerbation of the disease. Similarly Toubi and Vadasz [19] reported a positive correlation between disease severity and the level of IL-17 as IL-17 can promote the release of inflammatory mediators and chemokines by skin cells, increase inflammation and vascular permeability, and thus exacerbate the formation of wheals and itching symptoms [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of urticaria involves the activation of mast cells, which in turn release multiple cytokines, leading to sensory nerve activation, vasodilation, and plasma extravasation (56). Chronic urticaria is characterized by increased eotaxin and MCP-1, which are indicative of an inflammatory response (57,58). Urticaria is mediated by mixed T helper (Th) 1/Th2-reactive lymphocytes, with Th1 cells primarily secreting IL-2 and Th2 cells secreting IL-10.…”
Section: Populations Both Immune and Non-immune Cells Which Playmentioning
confidence: 99%